The physics of badminton - Cohen, C.; Darbois Texier, B.; Quéré, D.; Clanet, C. (New Journal of Physics, 2015)
The conical shape of a shuttlecock allows it to flip on impact. As a light and extended particle, it flies with a pure drag trajectory. We first study the flip phenomenon and the dynamics of the flight and then discuss the implications on the game. Lastly, a possible classification of different shots is proposed